The impact of some economic variables on the unemployment rate in Iraq for the period 2003/2014 - Diaa Hussein Saud (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The problem of unemployment is one of the main problems that impede the movement of economic development, as most countries of the world face different levels of progress and their economic, social and political systems, Iraq is one of those countries suffering from this problem, which was exacerbated by the extraordinary circumstances of the country’s economy, , And this problem is exacerbated by its persistence and existence for a long time with high rates. In 2003, the unemployment rate (28.10%) and its losses were in various forms and types in view of the continued weakness of the economic sectors’ ability to absorb the increasing number of public hands, This research aims to shed light on the nature of this problem to analyze and identify the causes and effects of serious and clarify the most important economic variables that affect the rate of unemployment through the use of statistical methods and standard, and then reach some conclusions and develop proposals that are appropriate to them and We find it necessary to reduce unemployment in Iraq.